2000
DOI: 10.12968/hosp.2000.61.2.1279
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of flexible training in medicine

Abstract: Most flexible trainees believe that their full-time colleagues perceive flexible training as flawed in some way. However, most consultants and full-time trainees actually view flexible trainees and their posts in a positive light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…There could be two reasons for this: those people harbouring negative attitudes might not have answered the survey or the perception of these attitudes could be greater than the reality. A survey of part‐time trainees and their colleagues and supervising consultants was performed in four different specialities 6 . The part‐time trainees believed that their training was perceived by their full‐time colleagues to be flawed in some way while the majority of consultants and full‐time trainees actually perceived flexible training positively.…”
Section: Discussionmentioning
confidence: 99%
“…There could be two reasons for this: those people harbouring negative attitudes might not have answered the survey or the perception of these attitudes could be greater than the reality. A survey of part‐time trainees and their colleagues and supervising consultants was performed in four different specialities 6 . The part‐time trainees believed that their training was perceived by their full‐time colleagues to be flawed in some way while the majority of consultants and full‐time trainees actually perceived flexible training positively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were found in a recent study in Australia [ 22 ]. However, Peters et al [ 26 ] showed that perceptions of negative attitudes from others among trainees working part-time, may not always be accurate. Although many flexible trainees experienced negative attitudes from their full-time colleagues, the majority of them appeared to have quite positive views towards flexible training.…”
Section: Introductionmentioning
confidence: 99%
“…Only around 4% of junior doctors in the United Kingdom are in flexible training posts,8 and negative images persist among both consultants and junior doctors 9. But imaginative schemes for job sharing in training posts have been introduced successfully in one postgraduate deanery,10 and flexible training has been advocated by associate postgraduate deans for years.…”
Section: Introducing Flexible Training and Workingmentioning
confidence: 99%